Ranolazine and Vernakalant Prevent Ventricular Arrhythmias in an Experimental Whole‐Heart Model of Short QT Syndrome. (13th July 2016) - FROMMEYER, GERRIT; ELLERMANN, CHRISTIAN; DECHERING, DIRK G.; KOCHHÄUSER, SIMON; BÖGEHOLZ, NILS; GÜNER, FATIH; LEITZ, PATRICK; POTT, CHRISTIAN; ECKARDT, LARS
Ranolazine and Vernakalant in Short QT Syndrome: Background: Ranolazine has been reported to have an antiarrhythmic potential. The aim of this study was to assess the electrophysiologic effects of ranolazine and to compare its effects to vernakalant in an experimental whole‐heart model of short‐QT syndrome. Methods: Rabbit hearts were isolated and Langendorff‐perfused. After obtaining baseline data, pinacidil, an IKATP channel opener, was administered (1 μM). Results: Endo‐ and epicardial monophasic action potentials and a 12‐lead ECG showed a significant abbreviation of QT interval (− 34 milliseconds, P < 0.05) and action potential duration (APD90 ; − 31 milliseconds, P < 0.05). This was accompanied by a reduction of effective refractory period (ERP; − 32 milliseconds, P < 0.05). Subsequently, hearts were additionally perfused with ranolazine (10 μM, n = 12) or vernakalant (10 μM, n = 14). Ranolazine led to an increase of QT‐interval (+ 29 milliseconds, P < 0.05), APD90 (+ 18 milliseconds, P < 0.05) and ERP (+ 28 milliseconds, P < 0.05) as compared with sole pinacidil treatment. Similar results were observed under the influence of vernakalant (APD90: + 25 milliseconds, QT‐interval: + 34 milliseconds, ERP: + 31 milliseconds). Under the influence of pinacidil, ventricular fibrillation (VF) was inducible by a standardized pacing protocol including programmed stimulation and aggressive burst stimulation in 8 of 12 hearts (ranolazine group, 34 episodes) and 7 of 14 hearts (vernakalant group, 24 episodes). Additional infusion of ranolazine (1 of 12 hearts, 1 episode) or vernakalant (1 of 14 hearts, 3 episodes) led to a significant suppression of VF. Conclusion: In the present pharmacologic model of short QT syndrome treatment with pinacidil led to an increased inducibility of VF in association with a reduction in ERP. Additional treatment with ranolazine or vernakalant reversed this effect and demonstrated potent antiarrhythmic properties based on an increase of ERP.